TINJAUAN UPAYA PENGELOLAAN LIMBAH SLURRY PADA PROYEK X - Kartika Hapsari; Arlisa Nurmala Mulyaningsih; Insan Kamal (Jurnal Ilmiah Teknologi Infomasi Terapan, 2025)
The slurry polymer waste generated from the development of project X poses a danger to the surrounding environment, namely in the form of water pollution, fires or explosions, and poisoning or negative effects on human health. Most importantly, it can damage the environmental ecosystem. The aim of this research is to identify effective, efficient, and environmentally friendly polymer slurry waste treatment. The method used in this study is to analyze primary data obtained directly from field observations and secondary data, namely the results of previous research from journals and data collected by the company. The results showed that the addition of chemicals to the slurry waste treatment process turned out to be more effective because it facilitated the quicker separation of the polymer particles and water mixed in the polymer slurry waste.